Mode matching technique for computation of resonance frequencies of composite metal-dielectric resonator (Visnyk NTUU KPI Seriia - Radiotekhnika Radioaparatobuduvannia, 2013)
The composite metal-dielectric resonator (CMDR) design is presented. An eigenproblem solution of the CMDR by mode matching technique is discussed. The problem is reduced to a set of homogeneous integral Fredholm equations of the first kind. The system is solved using Galerkin method. The technique is more efficient than FEM in terms of computational resources due to low rank of the system. It is shown that changing the air gap width between the dielectric and the metal plate provides the resonant frequency tuning. It is also shown that in order to achieve efficient electromechanical tuning of the CMDR resonant frequency, the resonant modes with a dominant electrical field component perpendicular to the air gap between the dielectric and the metal plate have to be selected. The tuning efficiency grows with the DR radius to thickness ratio and increasing permittivity. The CMDR can be used for creating compact high-Q micromechanical-tuned radiofrequency devices with wide tuning range.